1996
DOI: 10.1084/jem.183.1.271
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi OspA is an arthropod-specific transmission-blocking Lyme disease vaccine.

Abstract: SummaryBorrelia burgdo~feri, the spirochetal agent of Lyme disease, is transmitted by Ixodes ticks. A vaccine based on B. burgdo~feri outer surface protein (Osp) A protects mice from spirochete infection. Here we report on the expression of OspA on spirochetes inside engorging ticks and relate OspA expression to antispirochetal immunity. Spirochetes in the gut of unfed nymphal ticks were stained by an OspA antibody, whereas in feeding ticks, the majority of spirochetes in the gut and salivary glands did not st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
354
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(366 citation statements)
references
References 13 publications
8
354
1
2
Order By: Relevance
“…However, the previous finding that a fraction of experimentally challenged AKR/N mice with high levels of OspC-specific Ab was able to resolve infection [20] and that IS from tick-or needle-infected mice prevent subsequent infection in naive recipients [4,5] suggested that inherent spirochetal defense mechanisms can be breached by more-potent and/or morewell-timed Ab responses. This has been most convincingly documented for Ab to OspA and OspC [10,16,20]. These two lipoproteins are known to be differentially expressed on spirochetes in the vector and mammalian hosts [9,14].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, the previous finding that a fraction of experimentally challenged AKR/N mice with high levels of OspC-specific Ab was able to resolve infection [20] and that IS from tick-or needle-infected mice prevent subsequent infection in naive recipients [4,5] suggested that inherent spirochetal defense mechanisms can be breached by more-potent and/or morewell-timed Ab responses. This has been most convincingly documented for Ab to OspA and OspC [10,16,20]. These two lipoproteins are known to be differentially expressed on spirochetes in the vector and mammalian hosts [9,14].…”
Section: Discussionmentioning
confidence: 84%
“…In fact, it was found that the pattern of osp gene expression in B. burgdorferi dramatically changes depending on the microenvironment and that some osp genes even cease expression in mammals. The latter is the case for ospA, which is dominantly expressed in spirochetes harbored in the gut of unfed ticks, but not in those seeding the vertebrate host [8][9][10][11]. In contrast, expression of other osp genes, e.g.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The population of spirochetes expands [156][157][158] and their protein synthesis alters [49,99,122,159,160]. Then, spirochetes migrate from the midgut to the salivary glands, allowing transmission into a new host.…”
Section: B Burgdorferi Infection Of Ticksmentioning
confidence: 99%